Once-weekly rifapentine and isoniazid for tuberculosis prevention in patients with HIV taking dolutegravir-based antiretroviral therapy: a phase 1/2 trial. Issue 6 (June 2020) - Dooley, Kelly E; Savic, Radojkam; Gupte, Akshay; Marzinke, Mark A; Zhang, Nan; Edward, Vinodh A; Wolf, Lisa; Sebe, Modulakgotla; Likoti, Morongwe; Fyvie, Mark J; Shibambo, Innocent; Beattie, Trevor; et al.
Summary: Background: Short-course preventive therapy with 12 doses of once-weekly rifapentine (900 mg) plus isoniazid (900 mg) could greatly improve tuberculosis control, especially in areas with high co-endemicity with HIV. However, a small previous trial of such therapy with dolutegravir in healthy, HIV-negative adults was halted early after two of the four patients developed serious adverse events. Because of the potential use of this therapy, and variable safety outcomes of tuberculosis drugs seen in patients with and without HIV, we aimed to characterise safety, pharmacokinetics, and virological suppression in adults who are HIV positive. Methods: DOLPHIN was a phase 1/2, single-arm trial done at The Aurum Institute (Tembisa Clinical Research Site, Tembisa, South Africa), with pharmacokinetic visits done at VxPharma (Pretoria, South Africa). Adults (≥18 years) with HIV infection and undetectable viral load (<40 copies per mL) after at least 8 weeks of efavirenz-based or dolutegravir-based regimens were recruited in three consecutive groups, subject to approval by the independent safety monitoring committee. Participants received 50 mg of daily dolutegravir in place of efavirenz for 8 weeks, then began once-weekly rifapentine (900 mg)–isoniazid (900 mg) for 12 weeks. Groups 1A (n=12) and 1B (n=18) had intensive dolutegravir pharmacokinetic sampling at week 8 (before rifapentine–isoniazid), at week 11 (after the third dose of rifapentine)–isoniazid and at week 16 after the eighth dose. Group 2 (n=30) were treated with the same schedule and had sparse dolutegravir pharmacokinetic sampling at weeks 8, 11, and 16. Participants were followed 4 weeks after completion of prophylactic tuberculosis treatment. HIV viral loads were measured at baseline and at weeks 11 and 24. Primary endpoints were adverse events (grade 3 or higher) and dolutegravir population pharmacokinetics, assessed in participants who began rifapentine–isoniazid. This trial was registered at ClinicalTrials.gov, NCT03435146 . Findings: Between Jan 24, 2018, and Nov 25, 2018, 61 participants were enrolled into three groups; one participant withdrew (from group 1A). 43 (70%) of 60 participants were women and all participants were black African. Median age was 40 years (IQR 35–48), CD4 cell count was 683 cells per μL (447–935), and body-mass index was 28·9 kg/m 2 (24·0–32·9). Three grade 3 adverse events occurred; two elevated creatinine and one hypertension. Rifapentine–isoniazid increased dolutegravir clearance by 36% (relative standard error 13%) resulting in a 26% decrease in dolutegravir area under the curve. Overall geometric mean ratio of trough concentrations with versus without rifapentine–isoniazid was 0·53 (90% CI 0·49–0·56) though this ratio varied by day after rifapentine–isoniazid dose. All but one trough value was above the 90% maximal inhibitory concentration for dolutegravir and HIV viral loads were less than 40 copies per mL in all patients. Interpretation: Our results suggest 12 doses of once-weekly rifapentine–isoniazid can be given for tuberculosis prophylaxis to patients with HIV taking dolutegravir-based antiretroviral therapy, without dose adjustments. Further exploration of the pharmacokinetics, safety, and efficacy in children and pharmacodynamics in individuals naive to antiretroviral therapy is needed. Funding: UNITAID.